Improving Cognitive Abilities Of Group A Children Through Number Cards At Uswatun Hasanah Paud In The 2024/2025 Academic Year - Nuryani, Nuryani; Hadi, Rusman; Eliyana, Eliyana (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Abstract. The purpose of this study is to determine the efforts to improve the cognitive abilities of children in Group A through the use of number cards at Uswatun Hasanah Early Childhood Education Center in the 2024/2025 academic year. The research method used is classroom action research with a research design from Kemmis and Mc. TaggartThe research results indicate that children's cognitive abilities, particularly their ability to recognize numbers, in Group B at Uswatun Hasanah Early Childhood Education Center can be improved through the use of number card media. In the pre-cycle, the classical completion rate (KK) achieved was only 27.7% or approximately 3 children out of 11, indicating that children's cognitive abilities, particularly their ability to recognize numbers, were still low. Subsequently, interventions were implemented in Cycle 1, resulting in an increase to 6 children or approximately 54.5%. However, this achievement still did not meet the success indicators expected by the researcher. Therefore, Cycle II was conducted, and it was found that there was an improvement in children's cognitive abilities, particularly their ability to recognize numbers, with approximately 9 children or around 81.8% achieving mastery. The study was terminated at Cycle II as it had already achieved the success indicators expected by the researcher. It can be concluded that using number card media can enhance children's cognitive abilities, particularly their ability to recognize numbers in early childhood. Keywords: Cognitive Abilities, Number Card Media